Monument of history in Gdynia – problems with protection of the main representative axis of the city - Sołtysik, Maria Jolanta (Protection of Cultural Heritage, 2019)
The Monument of History in Gdynia encompasses the part of the City Centre shaped in the interwar period, whose important part is the establishment of the South Pier together with the Yacht Harbour and John Paul II Avenue. The spatial idea of this complex was presented in 1938, in the project of the so-called Representative District, which is a very original realization of the scenic opening of the city to the port and the sea. Since this urban development was not completed in the interwar period, it is now under strong investment pressure, especially in the area of the sailing center. The current local plan (2009, amended in 2015) unfortunately allows for a compact way of development, contrary to the historical concept of a loose and open sea system. Although the establishment of the South Pier has been included in the register of monuments since 2007, the procedures for its protection have failed, as evidenced by the results of the architectural competition held in 2014. The solution that could protect us from planning errors should be a "conservation plan for the management of the Monument of History", modelled on similar plans for the management of objects included in the World Heritage List and preceding granting the status of the Monument of History.